2019
DOI: 10.3329/pa.v29i4.41348
|View full text |Cite
|
Sign up to set email alerts
|

Study on indiscriminate use of antibiotics in poultry feed and residues in broilers of Mymensingh city in Bangladesh

Abstract: Abstract Knowledge, attitude and practice of broiler sellers about the indiscriminate use of antibiotic in poultry feed and antibiotic residue status of broiler in the live bird market of Mymensingh city was investigated. Twenty live poultry selling shops were randomly interviewed and six broilers from each market (5x6= 30) were randomly selected for detection of residual antibiotics in the liver and breast muscle. All the broiler meat sellers were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 11 publications
1
17
0
4
Order By: Relevance
“…Most of the small-scale layer farmers (94.16%) use antibiotics without prescription and do not maintain the withdrawal period of drugs [ 25 ]. Besides the farms, the poultry meat sellers in live bird markets (LBMs) also use different types of antibiotic to prevent unwanted mortality [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most of the small-scale layer farmers (94.16%) use antibiotics without prescription and do not maintain the withdrawal period of drugs [ 25 ]. Besides the farms, the poultry meat sellers in live bird markets (LBMs) also use different types of antibiotic to prevent unwanted mortality [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another study in Bangladesh among small-scale layer farms of Mymensingh district revealed that almost all (94%) farmers were using antibiotics without maintaining the minimum withdrawal period before marketing (25). Residues of ampicillin, ciprofloxacin and enrofloxacin have been detected in liver and meat of broilers (26). The presence of antibiotic residues in meat poses further risks to human health (27).…”
Section: Discussionmentioning
confidence: 99%
“…This is likely due to the high poultry farm density (N~520) compared with surrounding regions (N~350) ( Jahan, S., personal communication, 2020). Indiscriminate antibiotic use is common in Bangladesh (Khan et al, 2018). As shown in Table 3 veterinarians prescribed access, watch, and reserve group antibiotics frequently.…”
Section: Discussionmentioning
confidence: 99%